Making Sanctuary for the Divine: Exploring Melissa Raphael’s Holocaust Theology - Pramuk, Christopher (Studies in Christian-Jewish Relations, 2017)
This article details the author’s experience introducing Melissa Raphael’s 2003 book, The Female Face of God in Auschwitz: A Jewish Feminist Theology of the Holocaust, to predominantly Christian undergraduate and graduate theology students, and makes the case that her work deserves greater attention in Catholic and Christian theological circles. In provocative ways that elude systematic categorization, Raphael’s sensitive retrieval and theological interpretation of death-camp narratives builds a bridge between the Jewish and Christian memory of God that comes to bear especially on the theodicy question as intensified in the suffering of women, children, and the planet Earth. The mystical and theopoetical character of Raphael's method finds deep, if unsettling, resonance in students from widely diverse backgrounds.